A 31-Year-Old Female with Inferior Paraparesis Upper Motor Neuron Type due to Destruction of Thoracic 6-7 Vertebrae due to Tuberculous Spondylitis : A Case Report - Muhammad Al Faatih; Widiastuti Widiastuti (Jurnal Kedokteran Diponegoro, 2024)
Background: Tuberculous (TB) Spondylitis results from the hematogenous spread of Mycobacterium Tuberculosis bacteria to the spinal blood vessels. The incidence of extrapulmonary tuberculosis in the world is 3%, of which 10% of cases are bone. This paper will describe the case of a patient with Inferior Paraparesis Upper Motor Neuron Type due to Destruction of Thoracic 6-7 Vertebrae due to Tuberculous Spondylitis at Dr. Moewardi General Hospital, Surakarta, Indonesia. In addition, this case can provide information to health services and be a step forward in discussing tuberculous spondylitis further. Purpose: This study aims to report the diagnosis and management of tuberculous spondylitis. Case  Presentation: A Female, 31 years old, presented with complaints of lower limb weakness felt four months before admission and associated with back pain. The patient’s consciousness was compos mentis. There were tenderness in the back midline and neurological deficits. There was a decrease in muscle strength in the lower extremities, both left and right and also a decrease in physiological reflexes in all four extremities. There was positive Babinski on the right side and positive clonus on both sides. Thoracolumbar MRI results showed destruction of the corpus of Thoracic 6&7 Vertebrae with gibbus deformity and kyphosis with a picture of soft tissue abscess. Conclusion: The patient was diagnosed with paraparesis inferior upper motor neuron type due to destruction of thoracic 6-7 vertebrae due to tuberculous spondylitis. Then she was treated and planned for laminectomy, PSF, debridement, and corpectomy.